FUNCTIONAL DYNAMICS OF MYOCARDIAL INJURY BIOMARKERS PRODUCTION DURING ACUTE ISOPRENALINE TREATMENT IN RATS - Gatarić, Nina; Ilic, Ana; Todorovic, Dusan; Mutavdzin, Slavica; Jakovljevic Uzelac, Jovana; Stankovic, Sanja; Djuric, Dragan (Medicinski podmladak, 2021)
Introduction: Isoprenaline s. isoproterenol (1-(3,4-dihydroxyphenyl)-2-isopropylaminoethanolhydrochloride; ISO), a synthetic β-adrenergic agonist, can be used to establish myocardial ischemia, cardiotoxicity, necrosis and/or an experimental model of infarction in rats. Aim: Determination of the dynamics of myocardial injury biomarkers production: aspartate transaminase (AST), lactate dehydrogenase (LDH), creatine kinase (CK), and high-sensitive troponin T (hsTnT) with changes on electrocardiogram (ECG) parameters during the subcutaneous aplication of ISO in male Wistar rats. Material and methods: All animals (n = 23) were divided into two groups: control group (n = 11) treated with a saline solution, during two consecutive days (0,2 ml/kg b.m. daily, s.c); and the ISO group (n = 12) treated with isoprenaline, during two consecutive days (85 mg/kg b.m. daily, s.c). Blood was drawn from the rat tail vein in both groups in order to determine serum activity levels of myocardial injury biomarkers, and an ECG (n= 6) was registered prior to the application as well as 48 h following the first dose of of saline solution or isoprenaline. Results: In comparison to the control, in which no significant enzyme activities elevation (p > 0.05) nor ECG changes were registered, ISO group presented a significant rise of two clinically significant biomarkers of acute myocardial injury/myocardial infarction (AMI), CK (p = 0.05) and hsTnT (p < 0.01) as well as an ST segment elevation, a patognomonic ECG change. Conclusion: Obtained results support previous studies, that isoprenaline represents an adequate experimental model for myocardial injury/AMI induction, and a „golden standard“ for evaluating potential cardioprotective effects of pharmacological and non-pharmacological therapeutic modalities, with the ultimate goal of lowering the degree of lesions and improving post-infarction myocardium function.